2022
DOI: 10.1038/s43856-022-00086-8
|View full text |Cite
|
Sign up to set email alerts
|

Prospective multicentre head-to-head validation of host blood transcriptomic biomarkers for pulmonary tuberculosis by real-time PCR

Abstract: Background Sensitive point-of-care screening tests are urgently needed to identify individuals at highest risk of tuberculosis. We prospectively tested performance of host-blood transcriptomic tuberculosis signatures. Methods Adults without suspicion of tuberculosis were recruited from five endemic South African communities. Eight parsimonious host-blood transcriptomic tuberculosis signatures were measured by microfluidic RT-qPCR at enrolment. Uppe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 50 publications
2
31
0
Order By: Relevance
“…A recent head-to-head qRT-PCR comparison of eight parsimonious signatures by Mendelsohn et al showed no signature met the minimal target for a triage test in whole blood specimens from over 3000 HIV-infected or uninfected South African adults, although 5 signatures (RISK11, RISK6, Roe1, Roe3 and Suliman4) met the optimal target in symptomatic HIV-uninfected participants, and four signatures (RISK11, Maertzdorf4, Suliman4, and Thompson5) in symptomatic HIV-infected participants. 45 Whether such signatures have any utility as a triage test only in symptomatic participants remains to be understood.…”
Section: Triage and Diagnosis Of Active Tbmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent head-to-head qRT-PCR comparison of eight parsimonious signatures by Mendelsohn et al showed no signature met the minimal target for a triage test in whole blood specimens from over 3000 HIV-infected or uninfected South African adults, although 5 signatures (RISK11, RISK6, Roe1, Roe3 and Suliman4) met the optimal target in symptomatic HIV-uninfected participants, and four signatures (RISK11, Maertzdorf4, Suliman4, and Thompson5) in symptomatic HIV-infected participants. 45 Whether such signatures have any utility as a triage test only in symptomatic participants remains to be understood.…”
Section: Triage and Diagnosis Of Active Tbmentioning
confidence: 99%
“…A recent prospective study similarly showed the prognostic performance of mRNA signatures could meet the target only in the short term. 49 …”
Section: Predicting Development Of Active Tbmentioning
confidence: 99%
See 3 more Smart Citations